Desenvolvimento de Sistemas Microparticulados Superparamagnéticos Gastro-resistentes para Diagnóstico e Terapêutica - Silva, Amanda Karine Andriola (2008)
This work aimed to develop a suitable magnetic system for administration by the oral route. In addition to that, it was intended to review the current uses of magnetic systems and the safety related to magnetic field exposure. Methods: Coprecipitation and emulsification/crosslinking were carried out in order to synthesize magnetite particles and to coat them, respectively. Results: According to literature review, it was found that magnetic particles present several properties such as magnetophoresis in magnetic field gradient, production of a surrounding magnetic field, and heat generation in alternated magnetic field. When the human organism is exposed to magnetic fields, several interaction mechanisms come into play. However, biological tissues present low magnetic susceptibility. As a result, the effects are not so remarkable. Concerning the development of a magnetic system for oral route, uncoated magnetite particles did undergo significant dissolution at gastric pH. On the other hand, such process was inhibited in the xylan-coated particles. Conclusions: Due to their different properties, magnetic systems have been widely used in biosciences. However, the consequent increased human exposure to magnetic fields has been considered relatively safe. Concerning the experimental work, it was developed a polymer-coated magnetic system. It may be very promising for administration by the oral route for therapy and diagnostic applications as dissolution at gastric pH hardly took place